Critical Affect Literacy: A Call to Action in a Trump Administration. (1st October 2020) - Bondy, Jennifer M.; Johnson, Brent E.
ABSTRACT: Political discourses and practices surrounding the current presidential administration are propagating familiar stereotypes of immigrants as "diseases, " "criminals, " and questionably "American." Emergent research and the news media are also reporting stories of hostility toward immigrants in schools and broader society that has been incited by such rhetoric and practices. This article proposes teacher educators concerned with social justice for immigrant youth should teach meaningfully about the controversial emotions surrounding immigration. More specifically, the authors hypothesize how critical affect literacy may be instructive for helping pre-service teachers address the polarized and controversial emotions swirling around immigration. After providing a brief overview of the current national context of schools, the authors discuss the literature on teacher education for immigration. They then describe critical affect literacy and highlight its promise for helping pre-service teachers understand and counter-act negative emotions directed at immigrant students in schools. The authors also provide examples of instructional activities that might engage critical affect literacy practices in teacher education classrooms. In doing so, the authors hope to advocate the power of emotion in teaching for social justice in an increasingly uncertain and combative political climate.